ANALISIS YURIDIS TERHADAP PERAN DESA DALAM PENCEGAHAN DAN PENURUNAN STUNTING TERINTEGRASI DESA TOPORE - Andi Sukrianto; Muhammad Rusli; Muhammad Halwan (IAIN Palopo, 2022)
The purpose of this study was to understand the role of the village in preventing and reducing integrated stunting in Topore Village, Papalan District, Mamuju Regency and to find out the obstacles encountered in preventing and reducing integrated stunting in Topore Village, Papalan District, Mamuju Maya Regency. The results of this study indicate that the role of the village in preventing and reducing stunting is integrated in Topore Village, Papalan District, Mamuju Regency based on Presidential Regulation Number 72 of 2021 concerning the Acceleration of Stunting Reduction and Mamuju District Regent Regulation Number 31 concerning Prevention and Reduction of Stunting integrated with carrying out convergence prevention of stunting through a work plan for the implementation of stunting prevention which includes maternal and child health intervention services; integrated nutritional counseling, provision of clean water and sanitation; social protection and early childhood services. Furthermore, related to the obstacles faced in preventing and reducing stunting in Topore village, including regarding the implementation of programs such as socialization that is not optimal regarding the different understanding of the community in responding to the problem of stunting, provision of food and vitamin supplements as part of supporting intervention activities that cannot be fulfilled properly as well as the culture and beliefs of society that considers a short child's body is often seen as a result of inheritance from their parents.